A Narrative Review of Preclinical In Vitro Studies Investigating microRNAs in Myocarditis - Olga Grodzka; Grzegorz Procyk; Małgorzata Wrzosek (Current Issues in Molecular Biology, 2024)
According to the World Health Organization’s statement, myocarditis is an inflammatory myocardium disease. Although an endometrial biopsy remains the diagnostic gold standard, it is an invasive procedure, and thus, cardiac magnetic resonance imaging has become more widely used and is called a non-invasive diagnostic gold standard. Myocarditis treatment is challenging, with primarily symptomatic therapies. An increasing number of studies are searching for novel diagnostic biomarkers and potential therapeutic targets. Microribonucleic acids (miRNAs) are small, non-coding RNA molecules that decrease gene expression by inhibiting the translation or promoting the degradation of complementary mRNAs. Their role in different fields of medicine has been recently extensively studied. This review discusses all relevant preclinical in vitro studies regarding microRNAs in myocarditis. We searched the PubMed database, and after excluding unsuitable studies and clinical and preclinical in vivo trials, we included and discussed 22 preclinical in vitro studies in this narrative review. Several microRNAs presented altered levels in myocarditis patients in comparison to healthy controls. Moreover, microRNAs influenced inflammation, cell apoptosis, and viral replication. Finally, microRNAs were also found to determine the level of myocardial damage. Further studies may show the vital role of microRNAs as novel therapeutic agents or diagnostic/prognostic biomarkers in myocarditis management.